Oxygen Saturation and Perfusion Index-Based Enhanced Critical Congenital Heart Disease Screening - Siefkes, Heather; Kair, Laura; Tancredi, Daniel J.; Vasquez, Brian; Garcia, Lorena; Bedford-Mu, Christa; Lakshminrusimha, Satyan (American Journal of Perinatology, 2020)
Objective To determine if addition of perfusion index (PIx) to oxygen saturation (SpO2) screening improves detection of critical congenital heart disease (CCHD) with systemic outflow obstruction.Study Design We determined screening thresholds for PIx and applied these to a cohort of newborns with and without congenital heart disease (CHD).Results A total of 123 normal and 21 CHD newborns (including five with critical systemic outflow obstruction) were enrolled. Four of these five critical systemic obstruction subjects passed SpO2-based screen. Four out of these five subjects failed PIx-based screen. The sensitivity for detection of systemic obstruction CCHD when compared with healthy infants increased from 20% (95% confidence interval [CI]: 1–72%) with SpO2 screening alone to 80% (95% CI: 28–100%) with combined SpO2-PIx screen. However, 2.44% of normal infants failed PIx screen.Conclusion Addition of PIx to SpO2 screening may detect additional cases of CCHD and further research is necessary to come up with optimal screening thresholds.
Keywords: critical congenital heart disease; screening; pulse oximetry; newborns